(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Introduction: Pediatric Minimally Invasive Surgery is a relatively newer concept in Bangladesh and started about 8 years ago. It took some time to gather sufficient expertise to start in the neonates. However, due to resource constraints we are to practice with conventional equipments and still performing soLaparoscopy in Neonates in Bangladeshme advanced procedures. We are one of the pioneers in neonatal laparoscopy in Bangladesh and this article will review the common procedures that we perform. Materials and methods: From 7, October 2005 to 30, June 2011, 1953 cases underwent laparoscopic/thoracoscopic procedures in our department of which 117 were neonates. We have used conventional 5 mm 30 cm instruments including 5 mm 30º telescope. First trocar was introduced by open method and CO2 was pressure was kept below 8 mmHg. Age, sex, indications, operative procedures, complications and outcomes are evaluated retrospectively. Results: Ages ranged from 3 days to 30days with males predominant (1: 0.56). Laparoscopy-assisted pullthrough for Hirschsprungs disease was the commonest procedure (71) followed by Pyloromyotomy (21), Inguinal hernia repair (15), Ovarian cystectomy (06) and Diaphragmatic hernia repair (03). Six cases needed conversion, port-site infection occurred in 5 cases and incisional hernia in one. Six cases of Georgesons operation developed sepsis needing colostomy and three (2.56% of total neonates) of them died. Follow up was from 3 months to 5 years. Twenty three out of 60 successful Georgesons operations had peri-anal excoriation persisting for initial 2-3 weeks. Forty six cases are now having normal bowel habits, seven having constipation, five occasional soiling and two fecal incontinence. One (6.66%) inguinal hernia recurred. Overall 70% had uneventful outcomes and 9.4% had serious complications including death. Conclusions: Laparoscopy can be done in neonates using basic instruments with reasonable outcomes in a developing country setting J. Paediatr. Surg. Bangladesh 4(1): 5-10, 2013 (January)